Gramsci and Languages: Unification, Diversity, Hegemony - Carlucci, Alessandro (Historical Materialism Book Series, 2013)
In Gramsci and Languages Alessandro Carlucci explores the origins and significance of Antonio Gramsci's interest in language, showing in particular how his experience of linguistic and cultural diversity contributed to the shaping of his intellectual and political profile.